Developing Assessment Instrument of Literacy and Numeracy in Elementary School - Ahmad Faishol; Waris; Fauzan Adhim (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to analyze the form of literacy and numeracy skill assessment instrument development that is in accordance with the level of thinking ability of grade 5 students of SD Negeri 01 Senduro. This research used Research and Development with the ADDIE model. Data analysis was carried out using qualitative data analysis consisting of data presentation, data reduction, data verification, and drawing conclusions. The results indicated that the literacy and numeracy assessment instruments developed for grade 5 students of SD Negeri 01 Senduro were proven to be relevant, contextual, and in accordance with the level of students' thinking abilities. In short, this development of literacy-numeracy instruments proved to be both relevant and effective, accurately capturing students' abilities through tasks that reflect their everyday experiences and educational environment, and suited to the level of students' thinking for improving the learning process.